O processo pré-transição para a aposentadoria : desenvolvimento de escalas psicométricas e correlatos psicossociais - Rafalski, Julia Carolina (2015)
The ageing of population and the decrease in natality and fertility rates contribute to the growth of the thematic of retirement in importance in areas such as health and public policies, organizational policies and social security. This work focuses on comprehending the pre-transition process of retirement in the perception, decision and planning phases, observing how demographic, work and health variables can influence this phasing. To do so, this dissertation is designed in three papers. The first is destined to the development and validation of the Perceptions of Future Retirement Scale (PFRS), which presented a 5 dimensions structure: Health Perceptions, Detachment from Work, Finances, Interpersonal Relationships and Losses in Retirement. The scale presented good internal reliability in all five subscales (above 0,70) and relation with other variables. The second paper presents the adaptation process of the Process of Retirement Planning Scale (PRePS) to Brazilianportuguese and it’s relation with decision-making styles. The PRePS was satisfactorily adapted and results show that decision-making styles are able to predict more retirement planning. The third paper focused on understanding how the three pre-transition to retirement phases relate to one another and to variables of mental health and work. Results showed that the variables predicting retirement planning are mutable depending on which dimension is being analyzed, but the ability of perceptions, reasons to retire and decisionmaking styles to predict planning was confirmed in all four dimensions (finances, lifestyle, psychosocial and health). Overall, this study confirmed the existence of the pre-retirement triad in the Brazilian population, focusing on the influence of demographic variables, such as age, and personal, such as perceptions, reasons to retire and decision-making styles in the following planning to life after work. The need of further research is clear, in order to verify the existence of other psychosocial variables that can be related to the retirement process in the Brazilian population.